Derivate fondamentali e regole di derivazione Flashcards
Derivata di f(x) = k
f’(x) = 0
Derivata di f(x) = x^n
f’(x) = n x^n-1
Derivata di f(x) = x
f’(x) = 1
Derivata di f(x) = ^n√x
f’(x) = 1/n * ^n√x^n-1
Derivata di f(x) = 1/x
f’(x) = - 1/x^2
Derivata di f(x) = √x
f’(x) = 1/2 * √x
Derivata di f(x) = sen(x)
f’(x) = cos(x)
Derivata di f(x) = cos(x)
f’(x) = -sen(x)
Derivata di f(x) = tg(x)
f’(x) = 1/cos^2(x) oppure 1+tg^2(x)
Derivata di f(x) = ctg(x)
f’(x) = - 1/sen^2(x) oppure -(1+ctg^2(x)
Derivata di f(x) = ln(x)
f’(x) = 1/x
Derivata di f(x) = a^x
f’(x) = a^x * ln(a)
Derivata di f(x) = e^x
f’(x) = e^x
Derivata di f(x) = arcsen(x)
f’(x) = 1/√1-x^2
Derivata di f(x) = arccos(x)
f’(x) = - 1/√1-x^2
Derivata di f(x) = arctg(x)
f’(x) = 1/1+x^2
f(x) = k*f(x)
f’(x) = k*f’(x)
f(x) = f(x) + g(x)
f’(x) = f’(x) + g’(x)
f(x) = f(x) * g(x)
f’(x) = f’(x)g(x) + f(x)g’(x)
f(x) = f(x)/g(x)
f’(x) = ( f’(x)g(x) - f(x)g’(x) )/ g(x)^2
f(x) = f(g(x))
f’(x) = f’(g(x)) * g’(x)
f(x) = (f(x))^n
f’(x) = n(f(x))^n-1 * f’(x)
f(x) = a^f(x)
f’(x) = a^f(x) * ln(a) * f’(x)
f(x) = e^f(x)
f’(x) = e^f(x) * f’(x)